Force plate testing is correlated wirth juping performance in elite nordic skiers - Vasavada, K. D.; Shankar, D. S.; Lin, C. C.; Rynecki, N. D.; Avila, A.; Buzin, S.; Chen, A. L.; Carter, C. W.; Borowski, L. E.; Milton, H. A.; Gonzalez-Lomas, G. (Journal of Cartilage & Joint Preservation, 2023)
Objective: The purpose of this study was to determine the relationship between force plate testing metrics, Functional Movement Screen (FMS) scores, and radiographic signs of FAI and ski jumping performance. Methods: Elite SJ and NC athletes were prospectively recruited. FMS testing was performed to assess muscular imbalance, instability, and immobility. Vertical jump testing was performed using a commercially-available force plate device. Ski jump score and distance score were measured on a single jump for each athlete. Results: Twenty-one athletes (10 SJ, 11 NC) with competition scores were included. On FMS testing, most SJ (67%) and NC (73%) athletes demonstrated core instability. There were higher rates of hip instability and ankle stiffness among SJ athletes, although not statistically significant (p>0.05). Ski jump distance score was significantly positively correlated with force plate vertical jump height, maximum acceleration, maximum velocity, concentric impulse, counter-movement depth, and flight time (p<0.05). FMS testing results and radiographic FAI were not significantly associated with competition scores. Conclusions: Our results show significant positive correlations between competition scores and force plate jump testing performance as measured by jump height, acceleration, maximum velocity, counter-movement depth, and concentric impulse in elite SJ and NC athletes. Our findings suggest that ski jumpers may benefit from training that emphasizes stretch-shortening cycles and eccentric-to-concentric contraction transition, which may optimize performance and promote joint stability.